Solving one pseudo-Volterra integral equation - Kosmakova, M.T.; Akhmanova, D.M.; Iskakov, S.A.; Tuleutaeva, Zh.M.; Kasymova, L.Zh. (Bulletin of the Karaganda University. Mathematics Series, 2019)
In this paper, we study the solvability of a second - kind pseudo-Volterra integral equation. By replacing the right - hand side and the unknown function, the integral equation is reduced to an integral equation, the kernel of which is not «compressible». Using the Laplace transform, the obtained equation is reduced to an ordinary first - order differential equation (linear). Its solution is found. The solution of the homogeneous integral equation corresponding to the original nonhomogeneous integral equation found in explicit form. Special cases of a homogeneous integral equation and its solutions are written for different values of the parameter k . Classes are indicated in which the integral equation has a solution. Singular integral equations were considered in works [1-3]. Their kernels were also «incompressible», but kernels had an another form. In this connection, the weight classes of the solution existence differ from the class of the solution existence for the equation considered in this work.